Crab Larvae Counter Using Image Processing - Furqan Zakiyabarsi; Muhammad Niswar; Zahir Zainuddin (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2019)
Very small larval size, high mortality rate of crab larvae, the absence of an accurate crab larva counter at affordable price, the density of larvae that are not known accurately, the ratio of feed that not in accordance with the number of larvae to damage water quality and cannibalism, water quality can not be adjusted to the density of distribution, and economically unprofitable both in terms of feed efficiency and buying and selling transactions. By knowing the number of crab larvae accurately the survival rate of crab larvae increases and is economically beneficial. In this study larvae counters were designed and developed. This tool uses digital imagery to detect and count the crab larvae zoea-1 phase. The accuracy of crab larva counter is 89,8%.